Respuesta :

Space

Answer:

[tex]x=\frac{-3d-9}{k-d}[/tex]

Step-by-step explanation:

Step 1: Write out equation

d(-3 + x) = kx + 9

Step 2: Distribute

-3d + dx = kx + 9

Step 3: Subtract dx on both sides

-3d = kx - dx + 9

Step 4: Subtract 9 on both sides

-3d - 9 = kx - dx

Step 5: Factor

-3d - 9 = x(k - d)

Step 6: Divide both sides by k - d

[tex]x=\frac{-3d-9}{k-d}[/tex]

Answer:

Step-by-step explanation:

Step 1: Write out equation

d(-3 + x) = kx + 9

Step 2: Distribute

-3d + dx = kx + 9

Step 3: Subtract dx on both sides

-3d = kx - dx + 9

Step 4: Subtract 9 on both sides

-3d - 9 = kx - dx

Step 5: Factor

-3d - 9 = x(k - d)

Step 6: Divide both sides by k - d